2021
DOI: 10.1016/j.reumae.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra as a potential alternative in the treatment of severe acute respiratory infection associated with SARS-CoV-2 refractory to tocilizumab

Abstract: SARS-CoV-2 is a new RNA virus which causes coronavirus disease 2019 (COVID-19), declared a pandemic by the World Health Organization (WHO). It triggers an atypical pneumonia that can progress to multiorgan failure. COVID-19 can cause dysregulation of the immune system, triggering an inflammatory response, and simulate haemophagocytic lymphohistiocytosis. Several studies have proposed that anti-IL-6 receptor antibodies, such as tocilizumab, play an important role in the treatment of severe acute respiratory inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Strikingly, in the latter study, tocilizumab decreases hospital-related mortality (HR: 0.64, 95%CI 0.47–0.87; p = 0.040). Conversely, reports of tocilizumab failure for COVID-19 have also been reported [ 28 30 ], and, in another study of 21 patients (matched to a historical control group using propensity score matching), such beneficial effect of tocilizumab was not outlined [ 31 ]. Yet, it should be emphasized that in the latter study, all patients received high-dose methylprednisolone —which might have skewed the study results—and the levels of oxygen therapy were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, in the latter study, tocilizumab decreases hospital-related mortality (HR: 0.64, 95%CI 0.47–0.87; p = 0.040). Conversely, reports of tocilizumab failure for COVID-19 have also been reported [ 28 30 ], and, in another study of 21 patients (matched to a historical control group using propensity score matching), such beneficial effect of tocilizumab was not outlined [ 31 ]. Yet, it should be emphasized that in the latter study, all patients received high-dose methylprednisolone —which might have skewed the study results—and the levels of oxygen therapy were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, gene expression analyses concur with these findings, i.e., IL-1-related proinflammatory pathways are highly upregulated in severe cases ( 151 ). Therefore, the IL-1 blockade treatment by anakinra (an anti-IL-1 receptor antagonist) may be an effective alternative option for COVID-19 patients ( 152 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…A recent study reported autoantibodies to cytokines as a marker for disease severity in COVID-19 [74], which has interest because of previous associations of anticytokine antibodies to infectious disease susceptibility and outcomes. In addition, there is increasing evidence that several drugs, such as IL-6 antagonists, that have been used in patients with HLH, MAS and other autoimmune/autoinflammatory conditions were beneficial in COVID-19 [75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Interestingly, autoimmune disease patients treated with anti-TNF alpha inhibitors do not show increased risk of COVID-19 infection or more severe disease cause [89].…”
Section: Link Between Covid-19 and Autoimmunitymentioning
confidence: 99%